Learning, Wage Dynamics, and Firm-Specific Human Capital - Felli, Leonardo; Harris, Christopher (Journal of Political Economy, 1996)
The authors introduce a dynamic and fully strategic model of wage determination in the presence of firm-specific human capital. In this model, human capital is interpreted as information. The authors show that equilibrium exists and is efficient and that it gives rise to a unique distribution of the social surplus. They show further that the equilibrium wage is determined by three factors. Consideration of these factors allows the authors to determine when and how the market mechanism enables the worker to capture some of the returns to firm-specific human capital. They relate their findings to the ongoing empirical debate concerning the return to tenure.